La banca electrónica y la satisfacción percibida por los clientes de la agencia Iquitos de Mibanco Banco de la Microempresa S.A. 2021 - Tapia Rojas, William Edgar (2023)
The present research work identifies the characteristics of the level of use of electronic banking (e-banking) and the level of satisfaction perceived by the clients of the Mibanco Iquitos Agency, in order to define strategies to face the competition and improve the positioning of Mibanco as a financial institution dedicated to small and microenterprises, in the process of technological convergence accelerated by covid-19. The research is of a quantitative type, a descriptive-correlational level and a non-experimental design. After obtaining data through the application of two surveys to 341 clients of Mibanco Iquitos Agency, it´s concluded that during the analyzed period the level of use of e-banking doesn´t present any correlation with the level of satisfaction perceived in said institution. for which a Spearman's Rho coefficient of 0.067 was obtained, and a p > t value of 0.215, which shows no statistical significance. Also, it was determined that the level of use of e-banking by customers is high, and its domain with the highest value is the training received, followed by security, and finally the use of electronic media; and, that the level of perceived satisfaction is high, and its domain with the highest value is the availability of the service, followed by responsibility, professionalism, and finally the speed of the transaction.